Group II mGlu receptor antagonist LY341495 enhances the antidepressant-like effects of ketamine in the forced swim test in rats - Podkowa, Karolina (Psychopharmacology (Berl), 2016)
RATIONALE: Numerous preclinical and clinical studies have reported the rapid and sustained antidepressant effects of the NMDA receptor antagonist ketamine. Because ketamine induces several undesirable and dangerous effects, a variety of strategies have been suggested to avoid such effects. OBJECTIVES: Here, we propose to enhance the sub-effective doses of ketamine by co-administration with the group II metabotropic glutamate (mGlu) receptor antagonist LY341495. This compound potentially acts as an antidepressant via a mechanism similar to that of ketamine. METHODS: To investigate the rapid and sustained antidepressant-like effects of these drugs, we administered ketamine and LY341495 individually or in combination, 40 min and 24 h before the forced swim test (FST). RESULTS: We found that sub-effective doses of ketamine and LY341495, given jointly, induce significant antidepressant-like effects, at both 40 min and 24 h after administration. The results obtained using Western blot technique indicate that mammalian target of rapamycin (mTOR) pathway activation may be involved in the mechanism of this action. The effects of drugs, used at identical ranges of times and doses, on spontaneous locomotor activity in rats were excluded. Furthermore, the results obtained from the rota-rod test and the ketamine-induced hyperlocomotion test suggest a lack of potentially adverse effects from the combined administration of ketamine and LY341495 at doses previously used in the FST. CONCLUSION: Altogether, these data suggest that the joint administration of ketamine and LY341495 might be a noteworthy alternative to the use of solely ketamine in the therapy of depression.